PENGARUH KOMPETENSI DAN MOTIVASI GURU TERHADAP KINERJA YANG DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH (Studi Kasus pada Guru SMA di Kabupaten Jepara) - Jamaluddin, 11.52.02.0018 (Students Journal of Economic and Management, 2013)
The research was carried out to examine the effect of competence and motivation of the Teacher Performance Moderated Leadership Principal of Senior High School in distric Jepara. The population of this research are State Senior High School Teachers in Jepara Regency with the 191 respondences by proportional random sampling technique. In order to examine this hypothesis, we use the linear regression empirical model quasi moderation with independent variables: Competence, Motivation, Principalâs Leadership and Teacherâs Performance as dependent variable. The results of the research show that all of the three independent variables: Competence, Motivation, Principalâs Leadership influence Teacherâs Performance simultaneously. The results of the data analysis show: (1) there is a positive and significant correlation between teacherâs competence and performance, (2) there is no correlation between teacherâs motivation and performance, (3) there is a positive and significant correlation between Principalâs Leadership and Teacherâs performance,(4) The Principalâs Leadership canât moderate the influence of the competence on Teacherâs Performance, (5) The Principalâs Leadership canâtÂ moderate the influence of the motivation on Teacherâs Performance. Keywords: Competence, Motivation, Principalâs Leadership and Teacherâs Performance